Tanggapan Penonton Terhadap Program President's Corner di Metro TV: Studi Deskriptif pada Warga Perumahan Maharaja Depok (Faculty of Communications Science, Dr. Soetomo University, 2018)
In the middle of the growing use of mass media in Indonesia, with the presence of internet and social media, but television is still the most popular media compared to other mass media. Metro TV is one of the television stations that is concerned with the quality of their program. This research talks about audience responses to President's Corner Program on Metro TV. The aim of research is to analyze the response of the audience to President's Corner using 3 dimensions of response, which are cognitive, affective and behavioral. This research use S-O-R theory as the main theory, and other supporting theory such as responses theory, the theory of mass communications effect, television and television program. The methodology used is descriptive quantitative using questioners distributed to 70 respondents with a total population of 229 residents of residents of Maharaja RW 14, Depok. The Scale used is the Likert scale. From the results of this research, it can be concluded that the response of the audience to President's Corner program is good, with cognitive average value at 4,17, affective 3,82, and behavior at 3,42. Keywords: Response, audience, television's program, quantitative, descriptive.